Pemetaan Kurikulum Program Studi Pendidikan Teknik Elektro Fakultas Teknik Universitas Negeri Padang untuk Memaksimalkan Kompetensi Lulusan - Putri, Media Syafrina; Mukhlidi, Mukhlidi (Minangkabau Scholar Institute, 2020)
This research is about mapping curriculum of Electrical Engineering Education Program, Faculty of Engineering, State University of Padang. The curriculum mapping program of Electrical Engineering Education Studies is conducted so that there is a coherent relationship between the material being taught and the student's expectation. The purpose of this research is to map the curriculum of PSPTE-FT UNP that characterize the standard of competence, mix the curriculum arranged according to the requirement of the student it will be easy for the study program to produce competent graduates who are ready to compete in work world. The results showed, with 53 sheets of courses with a weight of 145 credits students can get a bachelor degree, in it including doing thesis in the final semester. With the sequence of proposal seminars and trial sessions of research results. Prior to the research, students received a bachelor's degree with a volume of 56 courses weighing 145 credits. But in the curriculum there are 3 courses that are not resolved. From the research results can be concluded with 53 courses with 145 credits better 56 courses weighing 145 credits.